French American British (FAB) morphological classification of childhood lymphoblastic leukaemia and its clinical importance. - Lilleyman, J; Hann, I; Stevens, R; Eden, O; Richards, S (1986)
As part of the Medical Research Council Leukaemia Trial UKALL VIII, 738 unselected children with acute lymphoblastic leukaemia (ALL) had the morphology of their marrow blast cells reviewed by a panel of three haematologists. Ninety four (13%) showed appearances classifiable as type L2 by the French American and British (FAB) cooperative group's criteria, five (0.7%) were typed L3, and the remaining 639 (86%) as L1. Disregarding the patients classified as L3, those with the L2 variant showed an inferior disease free survival to that of the remainder (p less than 0.01), and more of them failed to remit after receiving "standard" remission induction treatment (p less than 0.01). They included an excess of older children (p less than 0.01) with less profound marrow failure at diagnosis, and fewer of them expressed the common ALL antigen (p = 0.05). There was no association between L2 morphology and the diagnostic white cell count, sex, or the presence of a mediastinal mass. These findings confirm earlier reports that FAB L2 ALL is associated with a poor prognosis and that it occurs more commonly in older children. The high remission failure rate is a recent observation and indicates that alternative early treatment may be appropriate for such patients.